(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The Impact of a Counseling Training Program on Developing Psychological Hardiness and Decision-Making Accuracy among Iraqi Football Referees. Psychological preparation is a decisive factor for football referees in managing matches and coping with increasing pressures. Psychological hardiness acts as a protective shield, enabling referees to view difficulties as challenges rather than threats. This study aims to evaluate the effectiveness of a proposed counseling training program in developing psychological hardiness dimensions (Commitment, Control, and Challenge) and enhancing decision-making accuracy among Iraqi football referees. An experimental approach was employed using an equal-groups design (experimental and control) with pre- and post-tests. The sample consisted of (50) first-class referees in Baghdad. Data were collected using the Psychological Hardiness Scale (Mukhaimer, 2006), a cognitive test for officiating situations, and an international decision-making accuracy form. Findings revealed significant post-test improvements in the experimental group, with overall psychological hardiness and decision-making accuracy levels increasing substantially compared to the control group. A statistically significant positive correlation was found between the development of commitment/challenge dimensions and enhanced decision accuracy. Conclusion: The proposed counseling program effectively contributes to building referees’ psychological stability, leading to higher field performance quality and faster information processing without hesitation.